From Woodstock to Glastonbury to the Isle of Wight: The Role of Festival Films in the Construction of the Countercultural Carnivalesque. Issue 2 (14th March 2020) - Anderton, Chris
ABSTRACT: This article examines the narrative construction of two British music festival films, Message to Love: the Isle of Wight Festival (1995) and Glastonbury Fayre (1972): films which demonstrate narratives and techniques familiar from Woodstock – Three Days of Peace and Music (1970). I argue that these films, which portray the 1970 Isle of Wight Festival and the 1971 Glastonbury Fayre, have helped to construct and reinforce what I refer to as the "countercultural carnivalesque" – a way of thinking about festival culture that is informed by a particular understanding of the youth counterculture of the late-1960s.